Ideology of the Global hegemony of the USA - N A Geidarov (Vestnik RUDN. International Relations, 2008)
The US policy is based on the realization of the country's national interests by the forces in power. American policy is based on various concepts of national interest, depending on the character of the relations between the United States, the European Union and Russia.